2022
DOI: 10.1002/pro.4458
|View full text |Cite
|
Sign up to set email alerts
|

In situ tools for chromatin structural epigenomics

Abstract: Technological progress over the past 15 years has fueled an explosion in genome‐wide chromatin profiling tools that take advantage of low‐cost short‐read sequencing technologies to map particular chromatin features. Here, we survey the recent development of epigenomic tools that provide precise positions of chromatin proteins genome‐wide in intact cells or nuclei. Some profiling tools are based on tethering Micrococcal Nuclease to chromatin proteins of interest in situ, whereas others similarly tether Tn5 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…ARTR-seq is also highly versatile and applicable for cell lines, tissues, and even clinical formaldehyde-fixed samples. Both inspired by CUT&Tag 49 , ARTR-seq displays distinct advantages compared to the recently reported RT&Tag 22 . First, ARTR-seq uses random primers to unbiasedly capture local signals, while RT&Tag uses oligo(dT) primer for RT, potentially losing signals from nonpolyadenylated RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…ARTR-seq is also highly versatile and applicable for cell lines, tissues, and even clinical formaldehyde-fixed samples. Both inspired by CUT&Tag 49 , ARTR-seq displays distinct advantages compared to the recently reported RT&Tag 22 . First, ARTR-seq uses random primers to unbiasedly capture local signals, while RT&Tag uses oligo(dT) primer for RT, potentially losing signals from nonpolyadenylated RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that RNAPII and H3K27ac chromatin profiling can be conveniently and inexpensively performed on FFPEs in single PCR tubes or directly on slides. We use only heat in a suitable buffer to reverse the cross-links while making the tissue sufficiently permeable, followed by modified versions of our CUT&Tag-direct protocol, which is routinely performed in many laboratories 23 , 64 . We found that data quality using low-salt tagmentation for antibody-tethered chromatin accessibility mapping is sufficient to distinguish cancer from normal tissues and resolve closely similar brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we have shown that RNAPII and H3K-27ac chromatin profiling can be conveniently and inexpensively performed on FFPEs in single PCR tubes. We use only heat in a suitable buffer to reverse the cross-links while making the tissue sufficiently permeable, followed by needle extraction and a slightly modified version of our CUT&Tag-direct protocol, which is routinely performed in many laboratories (19,46). We found that data quality using low-salt tagmentation for antibody-tethered chromatin accessibility mapping is sufficient to distinguish cancer from normal tissues and resolve closely similar brain tumors.…”
Section: Discussionmentioning
confidence: 99%